Probiotic Bacilli Inhibit Salmonella Biofilm Formation Without Killing Planktonic Cells - Tazehabadi, Mahtab Hassanpour; Algburi, Ammar; Popov, Igor V.; Ermakov, Alexey M.; Chistyakov, Vladimir A.; Prazdnova, Evgeniya V.; Weeks, Richard; Chikindas, Michael L. (Frontiers in Microbiology, 2021)
Salmonellosis is a foodborne infection caused by Salmonella. Domestic poultry species are one of the main reservoirs of Salmonella, which causes the foodborne infection salmonellosis, and are responsible for many cases of animal-to-human transmission. Keeping backyard chickens is now a growing trend, increasing the frequency of direct contact with the flock and, by consequence, the incidence of Salmonella infections. Bacillus subtilis KATMIRA1933 and Bacillus amyloliquefaciens B-1895 are probiotic bacilli that produce the bacteriocins subtilosin A and subtilin, respectively. The antimicrobial activity of the two strains was determined against the reference strain Micrococcus luteus ATCC 10420. The cell-free supernatant of B. subtilis KATMIRA1933 inhibited biofilm formation by Salmonella enterica subsp. enterica serovar Hadar, Salmonella enterica subsp. enterica serovar Enteritidis phage type 4, and Salmonella enterica subsp. enterica serovar Thompson by 51.1%, 48.3%, and 56.9%, respectively. The cell-free supernatant of B. amyloliquefaciens B-1895 inhibited the biofilm formation of these Salmonella strains by 30.4%, 28.6%, and 35.5%, respectively. These findings suggest that the bacillus strains may have the potential to be used as probiotics and antibiotic alternatives for the control of Salmonella in poultry. The number of planktonic cells was unaffected by treatment with the cell-free supernatant. A co-culture of the Salmonella strains with either bacilli showed no signs of growth inhibition, suggesting that it might have been quorum sensing that is affected by the two Bacillus strains.